Pengaruh Media Sosial, Kualitas Layanan, Dan Pengalaman Wisata Berkesan Terhadap Niat Kunjungan Kembali Wisatawan - Putri, Elsya Erviany; Hanartyo, Ernawan Dwi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
Indonesian tourism makes a significant contribution to the Indonesian economy, thus having a positive impact on the growth of the tourism industry. This research aims to analyze the influence of social media, service quality and memorable tourist experiences on return visit intentions. Quantitative method with cross-sectional survey method used in this research, as many as 110 respondents were selected using purposive sampling technique based on certain criteria consisting of tourists aged 17-40 years, domiciled in Jakarta, and had visited the National Monument and National Museum in the last six months. Although previous research reveals the mediating role of memorable tourism experiences on return visit intentions, not many have examined the influence of social media and service quality together. The results show that social media has a significant influence on return visit intentions. Service quality also has a significant influence on return visit intentions. Memorable tourism experiences also have a significant influence on tourists' return visit intentions. This research can also be expanded by adding other variables that can influence tourists' revisit intentions, such as motivation, price, or destination image. In addition, further research could consider the mediating role of other variables, for example tourist satisfaction as a mediator between memorable tourism experiences and return visit intentions.